Tradisi Siat Sambuk di Banjar Pohgending Desa Pitra Ditinjau Dari Nilai-Nilai Pendidikan Agama Hindu - Harsana, I Ketut Gede (Jurnal Penelitian Agama Hindu, 2025)
This research aims to analyze the values ​​of Hindu religious education contained in the siat sambuk tradition in Banjar Pohgending, Pitra Village, Penebel District, Tabanan Regency, Bali, as well as its contribution to cultural preservation and development of the spiritual character of the community. The siat sambuk tradition, which is held every Pengerupukan Day before Nyepi, involves young people in a symbolic "war" using burnt coconut shells, aimed at neutralizing negative energy and maintaining eternal harmony. With a qualitative descriptive approach, this research collected data through observation, semi-structured interviews, and documentation studies, analyzed using the Miles and Huberman model. The research results show that this tradition is rich in the values ​​of Tattwa (philosophy of truth and belief in God), Susila (ethics and controlling emotions such as anger), and Ceremonies (purification rituals through offerings and processions such as Melasti and Tawur Agung Kesanga). This tradition is not only a cultural heritage, but also an effective educational medium that strengthens Balinese Hindu identity, trains discipline, respects ancestors and social togetherness. This study fills the void of previous academic studies with a special focus on the value of Hindu religious education in the siat sambuk tradition, while encouraging the preservation of local culture through the involvement of the younger generation. Thus, this tradition contributes to the formation of character, morality and spirituality, as well as maintaining the continuity of Balinese cultural identity in the context of modern life.